Measurements of Underwater Explosive Source Levels for Yields of 0.0012 to 126 Pounds - Buck, Beaumont M.; Magnuson, Albert W. (1971)
The equivalence of using energy measurements for explosives and intensity for CW sources in the determination of underwater acoustic transmission loss has been previously investigated by Hasse and Stockhausen for one-pound TNT changes. It was concluded that use of Weston's theoretically derived energy source levels was satisfactory for this size charge. The objective of the present experiment was to investigate the applicability of Weston's predictions of energy source level for a broader range of charge yields in view of estimates by Arons and others that the range at which an explosive signal propagates as an acoustic wave is critically dependent on charge yield. Shot energy source levels were determined by measuring received signal energy and then adding transmission loss values for path which were using a constant wave projector. It was found that, within the accuracy limits of the experiment, Weston's 'sum' formula is a close representation of the true energy source level of explosives in the yield range of 0.0012 to 126 pounds TNT above frequency equal to about the first bubble pulse frequency and is therefore usable for transmission loss determinations.